Anticipation of Aversive Visual Stimuli Is Associated With Increased Insula Activation in Anxiety-Prone Subjects - Simmons, Alan; Strigo, Irina; Matthews, Scott C.; Paulus, Martin P.; Stein, Murray B. (Biological psychiatry (1969), 2006)
Anticipation is a critical component of affective processing in general and for anxiety in particular. Prior research suggests that the right insula plays an important role in anticipation of affective processing during aversive images. This study aimed to test the hypothesis that individuals with increased anxiety-related temperamental traits (anxiety-prone [AP]) relative to anxiety-normative (AN) subjects would show an exaggerated insula response during anticipation of an aversive image. 16 AP and 16 AN individuals performed a task in the functional magnetic resonance imaging scanner, during which they viewed pictures of spiders and snakes. Subjects were prompted 4–6 sec before the onset of each aversive image. Blood oxygenation level-dependent signal was contrasted during cued anticipation of images versus non-anticipatory task performance as well as viewing images. As hypothesized, AP subjects showed greater response than AN subjects in the bilateral insula during anticipation. In addition, these individuals had lower activity within the superior/medial frontal gyrus. During the image presentation phase, AN subjects showed greater activation than AP subjects in the bilateral temporal lobes and left superior frontal gyrus. Moreover, bilateral temporal lobe activation during image presentation was inversely correlated with bilateral insula activation during anticipation both within groups and in the combined group. These data suggest that greater activation of the insula during visual anticipation is associated with visual processing of aversive stimuli in AP individuals. Insula hyperactivity might be a common feature in persons with elevated trait anxiety and, as such, might be a neuroimaging marker for anxiety proneness.